SEARCH FOR DISEASE IDENTIFICATION IN CITRULLUS LANATUS PLANTS WITH CERTAINTY FACTOR - Dina Apriani; Novica Irawati; Akmal Nasution (Jurnal Teknik Informatika (Jutif), 2022)
Citrullus Lanatus is the Latin word for watermelon plant.Citrullus Lanatus is a summer plant that requires a tropical climate for its growth. Diseases in plants are always found in every plant is not foreign to farmers, but the problem is whether the disease causes significant losses or not. Sometimes farmers know that their crops are attacked by disease, but farmers do not know what disease is attacking their crops. Most of Citrullus Lanatus farmers do not know much about the symptoms of disease in watermelon plants and as a result it causes crop failure due to errors in handling and choosing drugs, the composition of drugs used to treat disease, maybe because the dose is too much, so the plants are damaged and some even die. This study uses the certaity factor method to show a measure of certainty to a fact or rule. With this system entitled citrulus lanatus disease identification tracing with certainty factor, it is possible to build an expert system application to identify citrulus lanatus disease with certainty factor, make it easier for Citrulus lanatus farmers to detect diseases in Citrulus lanatus plants.